EVALUASI IMPLEMENTASI SISTEM INFORMASI MANAJEMEN DAERAH TERHADAP PENGELOLAAN DATA KEUANGAN PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KOTA MANADO - Junus, Wigia A.L.; Kalangi, Lintje; Suwetja, I Gede (Universitas Sam Ratulangi, 2017)
This study aims to evaluate the implementation of SIMDA to the management of financial data at the Regional Finance and Asset Management Board (BPK-AD) Manado City is in accordance with the general principles of local financial management. SIMDA is an application developed by BPKP to simplify regional financial management tasks. The research method used in this research is qualitative research by using interview technique with key informant, direct observation to the symptoms that appear in BPK-AD of Manado City and documentation study on related documents. The data collected were analyzed by descriptive method. The result of the research shows that the implementation of financial SIMDA to the management of financial data at Manado Finance and Regional Management Board (BPK-AD) of Manado City has not been fully in accordance with the general principle of local financial management. Keywords: Implementation of SIMDA, management of financial data, and general principles of local financial management.